Sample separation and the sensitivity of investment to cash flow: Is the monotonicity condition empirically satisfied? - Alfonsina Iona; Leone Leonida (Queen Mary University of London, School of Economics and Finance, 2018)
This paper studies whether the monotonicity condition of the investment-cash flow sensitivity is satisfied empirically. We show that if this condition holds, then the point of sample separation does not affect the monotonic relationship between the sensitivities of any two complementary classes of observations. Our test, based upon observable averages of the investment-cash flow sensitivity, rejects the monotonicity condition for any common metric of financing constraints we use. The testing procedure we propose reconciles the conflicting findings of the literature about the shape of the investment-cash flow sensitivity.
Keywords: G30; G32; 330; Investment-cash flow sensitivity; Monotonicity condition; Sample separation